2019
DOI: 10.1039/c9ra00268e
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of l-phenylalanine amino acid: electrostatic induced hindrance of fibril formation

Abstract: Nanostructure morphology originating from the self-assembly of molecules has attracted substantial attention due to its role in toxic amyloid fibril formation and immense potential in the design and fabrication of novel biomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 76 publications
(120 reference statements)
1
47
0
Order By: Relevance
“…The clear positive signal observed at 222 nm, also observed in previous studies of L-phenylalanine derivatives, was assigned to π-π* transitions resulting from aromatic stacking of the phenylalanine residues. 69 Hence, the self-organization into supramolecular structures of MAm-GFF was attributed to aromatic stacking interactions between FF moieties. In addition, recent experimental and theoretical studies suggested that the self-assembled nanostructures formed from FF-containing molecules are also stabilized via H bonding (FF-FF, FF-solvent) and other weak forces such as hydrophobic, electrostatic and Van der Waals interactions between non-polar moieties.…”
Section: Methacrylamide-functionalized Peptide Monomer Mam-gffmentioning
confidence: 99%
“…The clear positive signal observed at 222 nm, also observed in previous studies of L-phenylalanine derivatives, was assigned to π-π* transitions resulting from aromatic stacking of the phenylalanine residues. 69 Hence, the self-organization into supramolecular structures of MAm-GFF was attributed to aromatic stacking interactions between FF moieties. In addition, recent experimental and theoretical studies suggested that the self-assembled nanostructures formed from FF-containing molecules are also stabilized via H bonding (FF-FF, FF-solvent) and other weak forces such as hydrophobic, electrostatic and Van der Waals interactions between non-polar moieties.…”
Section: Methacrylamide-functionalized Peptide Monomer Mam-gffmentioning
confidence: 99%
“…Not surprisingly, later studies demonstrated the influence of the charged state of Phe ends on the morphology of the aggregates. In particular, in its zwitterionic state, Phe self-assembles into nanostructures with a fibrillary morphology, while in its cationic and anionic state, its aggregates are dominated by a flake morphology ( Tomar et al, 2019 ). Moreover, several studies were also oriented to investigate different aggregation properties and kinetics of L and D -Phe.…”
Section: Going Small: Oligopeptide-based Cross-β Assemblies For Biomamentioning
confidence: 99%
“…44,45 It was observed that FF and its congeners are able to self-organize into a large variety of NSs from nanotubes to nanofibrils, vesicles, and HGs. [46][47][48] The morphological variability of NSs depends on the experimental procedure adopted for their preparation such as the polarity of the solvent, 49 the pH value or temperature, 50 and by chemical modifications of the aromatic homodimer, including the addition/modification of residues in the sequence, and/or modification of peptide termini. 51,52 Recently, several examples of the HGs based on FF peptide 53 and on its analogues 54 have emerged in literature as potential carriers for the delivery of Dox.…”
Section: Ultra-short and Short Peptide-based Hgsmentioning
confidence: 99%